2001
DOI: 10.1097/00005768-200112000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Hypovolemic intolerance to lower body negative pressure in female runners

Abstract: We conclude that exercise-trained females have a high incidence of orthostatic intolerance during LBNP, with a greater reduction of SV independent of changes in baroreflex and neurohumoral function. A lower incidence of LBNP intolerance in UT may be accounted for by a lower reduction of SV during LBNP. An increase in leg compliance in the exercise-trained females may play an important role in inducing pronounced reduction of SV and hence the intolerance to LBNP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 18 publications
4
11
1
Order By: Relevance
“…All investigations demonstrating either negative or neutral effects of aerobic exercise involved the examination of very intense training in young athletes (VO 2 max > 60 mL·kg −1 ·min −1 ) 7-10 and most involved a cross-sectional design. [8][9][10] The only study that involved both a prospective intervention and a subject population of nonathletes demonstrated a large improvement in orthostatic tolerance to upright tilting in young adult military recruits, congruent with the results of this study. 6 To our knowledge, our study is the first to show that even older adults at very high cardiovascular risk due to type 2 diabetes, and age can improve orthostatic tolerance with regular aerobic exercise.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…All investigations demonstrating either negative or neutral effects of aerobic exercise involved the examination of very intense training in young athletes (VO 2 max > 60 mL·kg −1 ·min −1 ) 7-10 and most involved a cross-sectional design. [8][9][10] The only study that involved both a prospective intervention and a subject population of nonathletes demonstrated a large improvement in orthostatic tolerance to upright tilting in young adult military recruits, congruent with the results of this study. 6 To our knowledge, our study is the first to show that even older adults at very high cardiovascular risk due to type 2 diabetes, and age can improve orthostatic tolerance with regular aerobic exercise.…”
Section: Discussionsupporting
confidence: 83%
“…Vigorous aerobic training has been shown to improve orthostatic tolerance in young normal subjects, 6 but some investigations have demonstrated a worsening [7][8][9] or no 10 effect of aerobic training on orthostatic tolerance. The impact of aerobic exercise on GTN-induced orthostatic intolerance in older adults with type 2 diabetes has not been previously examined.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to being a direct vasoconstrictor, angiotensin II increases norepinephrine release from adrenergic nerve terminals and augments the postsynaptic response (29, 30a). Plasma renin activity (PRA) normally increases in response to an orthostatic challenge (12,26,27,41), but this response may be attenuated in some POTS patients (18,21). Jacob et al (18) observed that a subgroup of POTS patients had significantly decreased supine and standing PRA compared with healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Such changes in the leg veins lead to a reduction of blood pressure with a decrease in cardiac filling. It has been thought, therefore, that leg venous distensibility is a determinant of orthostatic tolerance in normothermic humans [41][42][43] . Muscle venous volume accounts for approximately 85% of the leg venous volume in normothermia 44,45) .…”
Section: Increase In Leg Venous Compliancementioning
confidence: 99%